MEDIA SOSIAL SEBAGAI KOMPONEN PEMBANGUN PERADABAN ISLAM - Lina Aniqoh (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2017)
The purpose of this paper is to examine da’wah strategy through social media type facebook and instagram by targeting Muslim teenager as object of da’wah. Teens must be empowered morally and spiritually because adolescents have a big part in determining the quality of civilization nation and religion. The result of this research reveals that da’wah strategy in facebook and instagram must be representative that is with creative way to be effective. Thus the purpose of communication propaganda that is the change of behavior, attitude or deeds with the content and hope of the message disampaiakn and the realization of the righteous deeds are deeds in harmony with messages (treatise) al-Quran and Sunnah will be more easily achieved. One of the simplest da’wah that can be done is by simple preaching through creative, unique and full-length video and video content with short video durations. With the moral and spiritual flight superior to Muslim teenagers, the necessity of Islamic civilization in pursuit of its glory will experience acceleration.